Kaji Eksperimental Pengaruh Campuran Bahan Bakar Bioetanol-Bensin Terhadap Unjuk Kerja Mesin SI - Asnawi Asnawi; Adi Setiawan; Muhammad Sayuthi; Tri Waluyo; Hagi Radian (Jurnal POLIMESIN, 2022)
Bioethanol is a clean fuel, renewable energy source that can be used in place of fossil fuels. Bioethanol has similar characteristics to gasoline fuel, making it an excellent alternative fuel for SI engines, contributing to the reduction of air pollution, the increased use of biofuels, and the removal of fossil fuel consumption. Analysis of the SI engine performance using gasoline fuel with an octane rating of 90 and gasoline-bioethanol blends containing up to 20% bioethanol concentration, each fuel blended at 5% by volume fraction. The purpose of this study is to present the experimental results for a spark ignition (SI) engine with a single injector that operates by using a gasoline-bioethanol blend as fuel. Analysis of the SI engine performance by using gasoline fuel with an octane rating of 90 and gasoline-bioethanol blends containing up to 20% bioethanol concentration. Each fuel was blended with bioethanol at an interval of 5% by volume fraction. The test was conducted on an SI engine with a capacity of 1500 cc, four cylinders, and a single injector was used to distribute fuel to each cylinder through the intake manifold. The shaft of the engine is connected to a 75 kW of eddy current dynamometer shaft to measure the engine torque. The engine load is controlled using an interface computer system. Load on an engine is done by increasing braking on the dynamometer, and real-time signals from the sensors are recorded. Each fuel sample is operated at full load or wide-open throttle (WOT) at speeds ranging from 1000 to 5500 revolutions per minute (rpm). The experiments show that adding bioethanol to gasoline fuel can have a significant effect on the single injector SI engine performance. When the bioethanol concentration of 10% (E10) by volume is used, it is possible to maintain engine power with lower fuel consumption or lower the energy supply to the engine cylinder, thereby increasing the thermal efficiency of the single-injector SI engine by 6.33% compared to gasoline fuel.